Nutraceuticals Past, Present and Future - Chávarri Hueda, María (IntechOpen, 2020)
Today's society is increasingly aware of the importance of food and health. For this reason, consumers increasingly demand more products that help prevent disease. In this sense, science and technology are helping to find new bioactive compounds that, when properly administered, can provide beneficial health effects. Among these compounds are nutraceuticals, concentrated natural bioactive substances available in pills, capsules, and powders among other forms. This book comprehensively reviews and compiles information on molecules that can help prevent and treat prevalent diseases.